Misyjny wymiar ikony Zesłanie Ducha Świętego - Sprutta, Justyna (Annales Missiologici Posnanienses, 2019)
The icon of The Descent of the Holy Spirit includes a mission message. The origins of the iconography of this mystery date back to the 6th century. The icon of Pentecost depicts the apostles, and an empty place between them, destined for the coming again of Jesus Christ. Adam was presented below, and then the pagans as representatives of the peoples and nations to whom the apostles are sent. Later in this place is presented Old King as a personifi cation of the Cosmos, that is here a personifi cation of all creatures. The apostles, as the fi rst missionaries, will proclaim the Gospel to this Cosmos.